1991
DOI: 10.1057/palgrave.jibs.8490315
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm Diversity, Organizational Learning, and Longevity in Global Strategic Alliances

Abstract: Abstract. Organizational theorists have correctly argued that the emergence and maintenance of robust cooperation between global strategic alliance partners is related to the diversity in the partners' characteristics. Yet previous research has failed to systematically delineate the important dimensions of interfirm diversity and integrate the dimensions into a unified framework of analysis. This paper develops a multilevel typology of interfirm diversity and focuses on organizational learning and adaptation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
542
2
51

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 864 publications
(603 citation statements)
references
References 24 publications
8
542
2
51
Order By: Relevance
“…While RBV-based research has highlighted the benefits of synergistic differences between partners, other work has stressed the potentially negative effects of differences, in particular cultural differences between partners, on joint venture longevity (Barkema, Bell, & Pennings, 1996;Park & Ungson, 1997;Parkhe, 1991). Much of this stream of research uses TCE logic and argues that differences between partners increase the costs of coordinating, monitoring, and acculturating partners and thus reduce an IJV's net value.…”
Section: The Impact Of Variety On Mpijv Dissolutionmentioning
confidence: 99%
“…While RBV-based research has highlighted the benefits of synergistic differences between partners, other work has stressed the potentially negative effects of differences, in particular cultural differences between partners, on joint venture longevity (Barkema, Bell, & Pennings, 1996;Park & Ungson, 1997;Parkhe, 1991). Much of this stream of research uses TCE logic and argues that differences between partners increase the costs of coordinating, monitoring, and acculturating partners and thus reduce an IJV's net value.…”
Section: The Impact Of Variety On Mpijv Dissolutionmentioning
confidence: 99%
“…Cultural distance adversely affects international joint ventures hy eroding the applicability of the parent's competencies (Johanson & Vahlne, 1977;cf. Brown, Rugman, & Verbeke, 1989;Chowdhury, 1992;Gomes-Casseres, 1989;Harrigan, 1985Harrigan, ,1988Hergert & Morris, 1988: Lorange & Roos, 1991Parkhe, 1991). Woodcock and Geringer (1991) argued that cultural differences produce inefficient principal-agent contracts, and Li and Guisinger (1991) found that U.S. affiliates whose partners came from culturally dissimilar countries were more likely to fail.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Here, after the strong increase in inter-firm constellations like strategic alliances and joint ventures in the 1980s, a wide range of studies on international cooperation between firms has emerged. In examining determinants of consortium performance, the study focuses on a unique aspect associated with the characteristics of partners involved in an alliance, namely interorganisational diversity (Parkhe 1991). An interesting paradox, which forms the core of the argument, is that alliances or consortia are based on both compatibility as well as complementarity.…”
Section: The Paradox Of Cooperation In a Global Environmentmentioning
confidence: 99%